(untitled) (Al-Academy, 2025)
In light of increasing environmental challenges, sustainable marketing has become a strategic necessity for brands. Interactive advertising has emerged as an innovative tool to promote this approach, combining technology and sustainability to effectively engage audiences. This study examines how interactive advertising can be used to promote sustainable practices. Interactive advertising has become an effective tool in modern marketing, combining interactivity and sustainability to enhance customer loyalty. This study highlights how interactive advertising—such as quizzes, augmented reality (AR), shoppable video, and personalized content—can enhance sustainable marketing for brands by fostering a deeper connection with consumers while promoting environmentally friendly and socially responsible practices. The second chapter presents a theoretical and analytical overview of the literature on the topic, including interactive advertising and sustainability: the concept, relationship, and characteristics; the concept of sustainable marketing and its dimensions; and the third chapter includes several conclusions, including that interactive advertising has the potential to transform the traditional marketing model into a sustainable model based on effective engagement. Interactive advertising is not just a marketing tool, but has become an ecosystem. The research also included a list of Arab and foreign sources